Perceived Effects of COVID-19 Pandemic on Food Security in Southeast Nigeria - Munonye, Jane; Osuji, Emeka; Olaolu, Michael; Okoisu, Anthony; Obi, Joy; Eze, Gladys; Ibrahim-Olesin, Sikiru; Njoku, Loveday; Amadi, Mark; Izuogu, Chibuzo; Azuamairo, Gillian (Frontiers in Sustainable Food Systems, 2022)
The study evaluated the effects of Covid 19 pandemic on food security in Southeast, Nigeria. Multi-stage random technique was used to select 209 households. Data for the study were analyzed using descriptive statistics, z-test, food security model, and tobit regression model. Results showed that the mean household size was 9.6 persons, which indicates a large household size. The percentage rate of food consumption of the households before the pandemic was higher relative to the Covid 19 event. Again, exorbitant prices of food materials were noticed during the Covid 19 as compared with before the pandemic. About 10.5% of the households met the minimum food requirements as proposed by World Health Organization, and Food Agriculture Organization as against the majority 76.1%. The three dimensions of food security which includes availability, accessibility and utilization were interposed by a number of factors such as artificial scarcity, increase in food prices, etc. Furthermore, social distancing, lockdown imposition, etc were important Covid 19 determinants of food security status of households in Southeast Nigeria. About 24% of the households were food secured compared to 76% that were in-secured during the pandemic. Robust and effective food and agricultural policy formulations and implementations were recommended in Southeast, Nigeria.